Uphoff 2018 PNAS: Real-time dynamics of mutagenesis reveal the chronology of DNA repair and damage tolerance responses in single cells - Uphoff, S (University of Oxford, 2018)
The data are described in the article “Real-time dynamics of mutagenesis reveal the chronology of DNA repair and damage tolerance responses in single cells”. The file names are composed of the strain name (see paper supplementary information) and the drug treatment specific to each experiment. Data are in MATLAB struct array format (.mat) with a separate line for each field of view. Each line is a struct array containing the following fields for each cell in the field of view: frames: frame indices drugTreatment: 1 for frames with drug treatment, 0 otherwise cellLength: segmented cell length in pixels cellArea: segmented cell area in pixels cellDivision: frame indices for cell division events CFP: average CFP (CFP3A) pixel intensity within segmented cell area (a.u.). YFP: average YFP (mYPet) pixel intensity within segmented cell area (a.u.) mCherry: average mCherry (mKate2) pixel intensity within segmented cell area (a.u.) foci: 1 for frames with a new MutL-mYPet focus, 0 otherwise